The Adaptation of Islamic Religious Education Teachers in Utilizing Digital Platforms for Learning Assessment in State Islamic Senior High Schools - Ansorul Alim; Suwadi Suwadi (MAN 4 Kota Pekanbaru, 2026)
This study analyzes the adaptation of Islamic Education (PAI) teachers in utilizing digital platforms for assessment at MAN 1 Kulon Progo. Employing a qualitative case study approach, data were collected through interviews with 4 participants (including PAI teachers and the Head of Madrasah), observations, and documentation. The findings reveal that teachers implemented a hybrid strategy: Jogja Madrasah Digital (JMD) for summative assessments and Quizizz/Kahoot for formative assessments. This process was supported by intensive leadership training and adequate laboratory infrastructure, which reduced technological resistance among senior teachers. In addressing connectivity issues and the digital equity challenges faced by boarding school students, teachers demonstrated adaptive expertise through the utilization of laboratory facilities. Theoretically, the study identifies a strong TPACK synthesis in transforming religious content into Higher-Order Thinking Skills (HOTS)-based assessment instruments. Although efficiency improved, affective assessment remains a challenge in digital automation. The success of this adaptation reflects the synergy between teacher agency, instructional leadership, and infrastructure, with recommendations for developing digital affective assessment rubrics that are more sensitive to spiritual and moral values.